Social determinants of overweight and obesity in the mother-child binomial: evidences from Mexico - Armando Arredondo; Christian Torres; Emanuel Orozco; Oscar Resendiz (BMC, 2020)
Abstract Background To analyze the influence of socioeconomic determinants on the development of overweight and obesity in the mother-child binomial. Methods This is a study based on a prospective cohort of the mother-child binomial. Using STATA software, the association between the mothers' body mass index and the nutritional status of minors was analyzed using a logistic regression model with socioeconomic and demographic variables. Results The combined prevalence of overweight and obesity in cohort mothers was 53.2%. A statistically significant association was found between the overweight mothers and minors with possible risk of overweight (p 0.001) and with overweight (p 0.001). The logistic regression model was adjusted by age and marital status and linked maternal overweight and obesity with the following variables: severe food insecurity (RR 1.17, CI 0.04-0.31), having a health problem (RR 1.5, CI 0.86-2.05), income (RR 1.79, CI .49-1.30), smoking (RR 1.1, CI 0.80-1.37) and dietary pattern (RR 1.5, CI 0.38-0.87). Conclusions The study highlights the importance of paying attention to risk factors starting at the gestational stage, since at this time the mother's nutritional status has an influence on the offspring's growth and development. Evidences exist of an association between intergenerational transmission of obesity and socioeconomic aspects of the mother. These evidences must be considered in the revision and adjustments to health system interventions for the prevention of obesity in the mother-child binomial.